2009
DOI: 10.1007/s00167-009-1003-x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous cement augmentation for the treatment of depression fractures of the tibial plateau

Abstract: The management of insufficiency fractures of the tibial plateau in osteoporotic patients can be very challenging, since it is difficult to achieve a stable fixation, an essential condition for the patients' early mobilization. We present a minimally invasive technique for the treatment of proximal tibial plateau fractures, ''tibiaplasty'', using percutaneous polymethylmethacrylate augmentation. Five osteoporotic patients (7 fractures) with a non-traumatic insufficiency tibial plateau fracture were treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
8
0
2
Order By: Relevance
“…Gleichwohl die ballonassistierte interne Reposition und Aufrichtung von Frakturen und die perkutane Verabreichung von Knochenzement zur Stabilisierung keine neuen Techniken sind, stellt die gemeinsame Anwendung beider Verfah-ren im Bereich des Tibiaplateau ein Verfahren dar, welches erst in letzter Zeit zusehends zur Anwendung kommt [1,10,14,19,25].…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…Gleichwohl die ballonassistierte interne Reposition und Aufrichtung von Frakturen und die perkutane Verabreichung von Knochenzement zur Stabilisierung keine neuen Techniken sind, stellt die gemeinsame Anwendung beider Verfah-ren im Bereich des Tibiaplateau ein Verfahren dar, welches erst in letzter Zeit zusehends zur Anwendung kommt [1,10,14,19,25].…”
Section: Diskussionunclassified
“…Zudem steigt das Risiko für Wundheilungsstörungen, Weichteilinfektionen wie auch Pseudarthrosen. Durch perkutane Verfahren lassen sich die den Knochen umgebenden Weichteile schützen [10].…”
Section: Diskussionunclassified
“…Furthermore, they recommended a minimal distance of 3 mm from the balloon to the articular surface, but in our opinion, even five millimeters are sufficient enough to elevate the impacted fragment in order to avoid subchondral or chondral exothermic damage [ 10 ]. Evangelopoulos et al [ 14 ] also reported good outcomes in seven atraumatic fractures of the tibial plateau in five osteoporotic patients. They highlighted the positive effect of minimal soft tissue damage and immediate full weight-bearing postoperatively by using pure PMMA.…”
Section: Discussionmentioning
confidence: 96%
“…It has been shown to have similar reduction capabilities as conventional mechanical tamps and can be used successfully to elevate tibial impressions [ 13 ]. Another advantage of this technique consists of the percutaneous approach without periosteal stripping/fenestration, which means a reduction in postoperative complications such as infections, delayed wound healing and pseudarthrosis [ 14 ]. Although the cement is rather expensive, it is still cheaper than other synthetic bone substitutes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] It has been found that arthroscopic assisted management of tibial plateau fractures allows early rehabilitation, short hospitals stay and low complications rate. [ 9 ] The open surgical technique demonstrated similar long term results and arthroscopy had no influence in the anatomical reduction. [ 10 11 ]…”
Section: Discussionmentioning
confidence: 99%